O império botânico: as políticas portuguesas para a flora da Bahia Atlântica Colonial (1768-1808) - Rodrigo Osorio Pereira (2013)
This thesis focuses on the relationship between the colonial botanic and the Portuguese crown policies related to the flora of Atlantic Bahia in the transition from the Eighteenth to the Nineteenth Centuries. By understanding modern science as an instrument of colonial domination, we verify that it assumed a major role in the Portuguese Overseas world. However, if on the one hand, botany served to enhance the exploitation of natural resources in the colonial horizon, on the other, it was assimilated by different local contexts and was reshaped with unique features which intensified the complexity of the relations between the center and peripheries. In the first part, we discuss the imperial relations between Portugal and Bahia from the botanic point of view, depicting its process of institutionalization in course in the Reign and the attractive factors for its consolidation in Bahia by pointing the staff of naturalists who worked there. To do so, we highlight the scientific institutions in Lisbon and Coimbra which organized an extensive network of the Portuguese naturalism. On the other side of the Atlantic, we focus on a part of the territory of the Captaincy of Bahia called Atlantic Bahia. It was considered as a strategic territory due to its connection with the Empire and was a botanical center. Numerous naturalists-employees developed their roles as agents of the Crown and as botanists there. They were: the Governor of the Captaincy of Bahia, Dom Fernando José de Portugal; the Ouvidor of the Comarca of Ilhéus, Francisco Nunes da Costa; the naturalist Manoel Ferreira da Câmara Bittencourt e Sá; the Captain of Infantry, Domingos Alves Branco Muniz Barreto; the Forest Conservator Judge, Baltasar da Silva Lisboa; the Juiz de Fora of Vila de Cachoeira, Joaquim de Amorim Castro; the philosopher José de Sá Bittencourt e Accioli and; the Director of the Botanical Garden of Bahia, Inácio Ferreira da Câmara Bittencourt. In the second part of the thesis we analyze how botany subsidized the construction of policies for the royal timber, agricultural crops and herbs in Atlantic Bahia, each one of these discussed in specific chapters. With regard to the royal timber, botany supported a sense of conservation of forests that resulted in rich surveys of species, a large number of studies and regulatory process for royal timber cuts. Regarding the crops, botany stimulated the creation of policies to diversify the agricultural potential of the region by indicating cotton as the major economical alternative. Finally, botanical studies enabled the creation of the Botanical Garden of Bahia, an institution inserted in the imperial network of circulation of herbs. In this second part we also highlight the factors which stimulated and/or limited botanical institutionalization in Bahia in the same period, directing attention to the strength of traditional crops and their noble elites in maintaining the status quo of sugar export.